The problem of access in suprarenal Ganglionneuroblastoma - Taha, Sami M.; Nugud, Ala Eldeen; Sharfi, Abdel Raoff; El Imam, Mohammed; Abrahim, Adil; Mustafa, Gamal (Gezira Journal of Health Sciences, 2011)
Ganglioneuroblastomas (GN) are benign, neurogenic tumors arising mainly from central or peripheral components of the autonomic nervous system. The tumor has a reported incidence of only 1–5% in the literature (1) They are rare compared with other benign neurogenic tumors, such as schwannomas and neurofibromas (2) . The common locations for neuroblastoma are adrenal gland, paraspinal retroperitoneum (sympathetic ganglia), posterior mediastinum, head, and neck. Locations such as the urinary bladder, bowel wall, abdominal wall, and gallbladder are considered unusual